Maternal and Fetal Outcomes among Pregnant Women with Preeclampsia after Receiving either Methyldopa or Methyldopa plus Nifedipine (Tanzania Medical Journal, 2022)
BackgroundGlobally, hypertension during pregnancy contributes to 10% of all pregnancy-related complications and is responsible for 10-15% of maternal mortality in low-middle income countries (LMIC) (1,2). This study aimed to assess maternal and fetal outcomes among pregnant women who were on Methyldopa (MD) or Methyldopa plus Nifedipine (MD + N) for preeclampsia (PE) and severe preeclampsia (SPE).MethodsThe study used prospective descriptive observation methods. It was conducted at Muhimbili National Hospital (MNH) maternity wards, involved pregnant women with moderate to severe PE on MD or MD + N admitted for labour from July 2016 to October 2016. A case report form (CRF) was used to record maternal demographics and clinical parameters including blood pressures, haemoglobin levels, platelets counts and proteinuria. While fetal outcomes assessed were fetal body weight, Apgar score, and mortality after delivery.ResultsThe average Mean Arterial Blood Pressure (MAP) for MD and MD + N patients on admission was recorded as 126.8 ± 12.5mmHg and 126.5 ± 14.73mmHg (p=0.879) and the day before delivery was 109.1 ± 9.6mmHg and 106.2 ± 11.0mmHg (p=0.061) respectively. Haemoglobin (Hb) level was 10.7±1.7mg/dl for MD group while 11.1 ± 1.4 mg/dl for MD + N group (p=0.114). Proteinuria in pregnant women on MD was 3 ± 1 while 2 ± 1 for MD+N (p=0.312). The count for stillbirth was 11.0% for MD and 16.7% for MD + N. Neonates with an Apgar score of <7 at five minutes after delivery was 11.0% for MD and 7.7% for MD + N.Conclusion Both methyldopa and methyldopa plus nifedipine treatment approaches are preferred to be adopted in LMIC in the management of PE and SPE and employed in all pregnant women at 28 to 34 weeks gestation age to have good and improved maternal and fetal outcomes. Close monitoring of fetal well-being is highly recommended in both groups when conservative management is preferred versus delivery when BP is not controlled. However, the use of methyldopa plus nifedipine in pregnant women with PE/SPE should be done with caution.